Experimental observations on some non-optimal materials from southern South America - Nami, Hugo Gabriel (2015)
Historically, lithic analyses and studies were based on the attributes and characteristics of artifacts derived from flint and/or flint-like materials. However, during the last decades, emphasis has been put on another rocks used for manufacturing stones tools; among others, quartzite, quartz, and other rocks with diverse fractures. Over the years, a number of experiments using varied flaking techniques and strategies were conducted in the Americas. In this endeavor, diverse non-flint-like materials were used to replicate varied core and bifacial reduction strategies. Among others, crystal quartz as well as varied acid and black volcanic rocks were flaked. The experimental observations allowed observing that several of these raw materials show subtle but different flaking qualities as well formal macroscopic attributes on the resulting products and by-products. Then, this paper presents and discusses some flaking qualities and attributes observed on some non-flint-like materials from South America.